The impact of fair value accounting on the behavior and trends of profit management in the banking sector in Sudan - Khaled, Walid Al Tayeb Omar (Arab Journal for Sciences and Research Publishing, 2016)
This study aimed to show the impact of fair value accounting on the behavior and trends of the management of profits in the banking sector by assessing the relationship between profit management and fair value under the accounting reservation as one of the contemporary accounting trends. To achieve the goal of the study, the qualitative and descriptive approach was followed in the analysis of the results that were obtained by questionnaire in a sample of the Sudanese banks that formed the study community, and the sample of the study was selected in the sample method (intended) to obtain certain opinions and information, and The number of (80) forms was distributed to the target sample. The study reached many results , the most important of which is that the use of fair value estimates in accounting measurement and disclosure provides a more objective and realistic method of performance of economic units, and that the flexibility of the application of accounting principles and the existence of multiple alternatives to accounting policies is a big reason for the existence of management Profits, the use of fair value estimates affects profit management and reduces them when using the accounting reservation policy and limits the motivations of opportunistic management to achieve their own motivations.
Keywords: fair value; profit management; accounting conservatism; Sudanese banks